Regiões do agronegócio e urbanização: implicações do uso do território pelas cooperativas agroindustriais no oeste paranaense - Marcos Xavier (Confins)
In this article, we present our considerations on the use of land by the agro-industrial cooperatives. We observe their forms of organization and its implications for the modernization of the territory and partitioning of geographical space, arising from such use. The observed result is the creation of competitive regions of specialized agribusiness in the production of soybeans, corn and animal protein. Noteworthy is the high degree of urbanization and the importance of the small towns where they are located of the technical and political production commands.